Australia's national disability insurance scheme: looking back to shape the future. Issue 9 (21st October 2017) - Kendrick, Michael; Ward, Margaret; Chenoweth, Lesley
Abstract: Australia's National Disability Insurance Scheme (NDIS) provides a once-in-a-generation opportunity to transform how people with a disability are served. Similar to the enactment of the Disability Services Act 1986, which challenged the segregation and supported the integration of people with a disability into community settings, the National Disability Insurance Scheme Act 2013 is expected to fundamentally disrupt traditional service practice and improve disabled people's lives. This paper identifies some lessons from the previous reforms of 1986 to guide policy makers, people with a disability, their families and service-providers, as they implement the NDIS now. It reflects on what it takes to make change, and what can be expected to remain essentially the same regardless of the disruption that the NDIS will bring. It concludes that if the lessons of the past hold true, the NDIS will require several decades of intentional leadership and capacity-building to achieve enduring, positive change.